Writing shame contemporary literature, gender and negative affect - Mitchell, Kaye (Edinburgh University Press, 2022)
Examines the intersection of shame, gender and writing in contemporary literatureConsiders the particular intersection of shame, gender and writing in literature produced since the 1990sViews shame as a constitutive factor in the social construction and experience of femininityAnalyses a diverse range of texts from pulp to literary fiction to life writing and autofiction, with a self-reflexive focus on the formal disjunctions produced by/in the writing of shame, and on the shame attending the act of writing itselfOffers political readings of neglected genres (lesbian pulp fiction), highly topical texts (like Kraus's I Love Dick and Knausgaard's My Struggle), and established authors (such as Mary Gaitskill and A.M. Homes)Through readings of an array of recent texts - literary and popular, fictional and autofictional, realist and experimental - this book maps out a contemporary, Western, shame culture. It unpicks the complex triangulation of shame, gender and writing, and intervenes forcefully in feminist and queer debates of the last three decades. Starting from the premise that shame cannot be overcome or abandoned, and that femininity and shame are utterly and necessarily imbricated, Writing Shame examines writing that explores and inhabits this state of shame, considering the dissonant effects of such explorations on and beyond the page